Mitigating Operational Risk in Community-Based Tourism: Evidence from Tugu Utara Tourism Village, Indonesia - Bahri, Asep Syaiful; Sugiarto; Hendratono, Tonny; Palupi, Santi; Amelia, Rizki; Jason, Jason (Journal of Tourism Sustainability, 2025)
Operational risk in a tourism village refers to failures or deviations in the execution of tourism activities, which, if left unaddressed, may escalate into reputational risks. This study investigates strategies for mitigating operational risks in Tugu Utara Tourism Village, Bogor Regency, West Java, Indonesia. Adopting a qualitative case study approach, data were collected through focus group discussions involving 15 key stakeholders, including tourism village managers, representatives from tourism village associations, and officials from the Bogor Regency Culture and Tourism Office. Thematic analysis was employed to identify and interpret patterns, with findings presented through fishbone diagrams and summary tables. Results reveal four core pillars for operational risk mitigation: system risk, human resource risk, internal risk, and infrastructure and supporting facilities risk. These findings contribute to the growing discourse on community-based tourism resilience by offering a contextualized framework for operational risk governance in rural destinations.